Benefícios da suplementação com L-Arginina em ratas Wistar submetidas à quimioterapia com 5-Fluorouracil - Fagiani, Marcela de Andrade Bernal (2018)
Cancer is considered the second leading cause of death in the world with treatment costs estimated at $150 billion by 2020. 5-Fluorouracil has been used in the treatment of cancer for more than 50 years since 1957, mainly in neoplasias of colon, stomach, esophagus, head and neck and prostate, which can cause side effects such as myelosuppression, immunosuppression, mucositis, weight loss and appetite as well as DNA damage. In order to minimize these undesirable effects, some nutrients that stimulate the immune response, such as L-arginine, have been studied, but the doses found in the literature have been used in humans and in studies with male rats, with differences in recommendations. The objective was to evaluate the effect of low doses of L-arginine supplementation on blood count, coagulation cascade, DNA integrity, spleen and jejunal inflammatory infiltrate in rats submitted to 5-fluorouracil chemotherapy. Thirty-two Wistar rats were fed ad libitum filtered water and fed commercially balanced feed, divided into 4 experimental groups containing 8 rats per group, which were distributed in two rats per box: normal control group was applied 1 mL of 0.9% physiological solution intraperitoneally to simulate the application of 5-FU in the other groups; G5-FU was applied a dose of 200 mg 5-FU/Kg; GArg50 and GArg100 a dose of 200 mg 5-FU/Kg was added and supplemented with 50 and 100 mg L-arginine/day, respectively, added into the drinking water ad libitum. After the chemotherapy in the rats, it was observed that: The G5-FU, GArg50 and GArg100 groups reduced the feed consumption, presenting similar consumption of the same, and the G5-FU presented reduction in the average water consumption. GArg50 group showed no weight loss, and the G5-FU and GArg100 groups lost weight. GArg50 presented polycythemia due to dehydration caused by diarrhea generated by 5-FU and in the hemogram, coagulation cascade and depletion in the spleen there was no difference of the G5-FU group. GArg100, reduced prothrombin time and depletion index in the spleen, increased the total leukocyte, eosinophil and lymphocyte counts. GArg100 still showed the highest total DNA damage index, and did not alleviate the inflammatory infiltrate in the gut, thus preventing the occurrence of mucositis, with the rats showing moderate inflammation in the jejunum. Supplementation with 100 mg L-arginine/day has the potential to minimize immunosuppression and depletion in the spleen caused by 5-FU chemotherapy. In addition, it can still act on the coagulation cascade, reducing blood coagulation time and contributing to DNA breakage generated by 5-FU. The dose of 50 and 100 mg of L-arginine/day, do not contribute to the reduction of mucositis in the intestine of rats.